2021
DOI: 10.1111/jog.15103
|View full text |Cite
|
Sign up to set email alerts
|

The giant steps in surgical downsizing toward a personalized treatment of vulvar cancer

Abstract: The present article aims to highlight the importance of changes of personalized surgical treatment for vulvar cancer. Current international literature regarding surgical treatment of vulvar cancer was evaluated. This included several studies and systematic reviews. Radical surgery approach, such as en bloc resection, was the first therapeutic option and the standard care for many years, even if burdened with a high complication rate and frequently disfiguring. Taussing and Way introduced radical vulvectomy app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…This was the conclusion, for example, of a U.S. study reporting a stable trend in 5-year overall and disease-specific survival from stage III–IV vulvar cancer between 1988 and 2007 [ 39 ]. An evolution towards less aggressive surgery has also been reported from Italy [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was the conclusion, for example, of a U.S. study reporting a stable trend in 5-year overall and disease-specific survival from stage III–IV vulvar cancer between 1988 and 2007 [ 39 ]. An evolution towards less aggressive surgery has also been reported from Italy [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the treatment in vulvar cancer today is to reduce the radicality and morbidity of this surgery [ 36 ], and several procedures have changed to induce a minimally invasive surgical approach, especially by introducing SLN biopsy, nicely presented in recent works [ 37 ]. Our study is one of the largest cohort studies performed to date, including 30 patients with a total of 99 SLN identified and evaluating a promising method of SLN detection.…”
Section: Discussionmentioning
confidence: 99%
“…16 The safety of cutting margins with smaller margins is also the subject of research. 17 Hence, in the future, clinicians should be more flexible in the use of radiotherapy and assess whether patients with VSCC of different etiological pathways need enhanced doses of VMAT or combined chemotherapy. Whether patients treated with surgery need routine postoperative adjuvant VMAT to avoid the side effects of radiotherapy while shortening the surgical margins to protect vulvar structures and functions and reduce the marginal recurrence rate.…”
Section: Dovepressmentioning
confidence: 99%